Billy Summers [compact disc, unabridged] : a novel - King, Stephen, 1947- (Simon & Schuster Audio, 2021)
Billy Summers is a man in a room with a gun. He's a killer for hire and the best in the business. But he'll do the job only if the target is a truly bad guy. And now Billy wants out. But first there is one last hit. Billy is among the best snipers in the world, a decorated Iraq war vet, a Houdini when it comes to vanishing after the job is done. So what could possibly go wrong?